Influence of density of dislocations in Ni and Fe on kinetics of anode process in chloride electrolyte - Alexey D Vasil’ev (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2012)
Inﬂuence of density of dislocations in Ni and Fe on kinetics of anode process in chloride electrolyte was studied. To create the increased density of dislocation this material was deformed by 15 %. It was discovered that the density of anode current increases several times with the increase of the density of dislocation. It was observed that the unevenness of dissolution of Ni anode increases with the increase of the density of dislocations in it.